Antarctic Krill Biomass and Flux Measured Using Wideband Echosounders and Acoustic Doppler Current Profilers on Submerged Moorings - Cutter, George R.; Reiss, Christian S.; Nylund, Sven; Watters, George M. (Frontiers in Marine Science, 2022)
During austral summer 2018/2019, we deployed an array of six submerged moorings equipped with Nortek Signature100 integrated wideband echosounder and acoustic Doppler current profilers (ADCPs) on the continental shelf of the northern Antarctic Peninsula. Acoustic data from these instruments were used to classify targets, estimate water flow and the biomass of Antarctic krill (Euphausia superba), and quantify krill flux (biomass transport). We differentiated krill from other target aggregations using a supervised classification of data from the echosounder representing five wideband frequency bins spanning 68 – 113 kHz and two narrowband frequencies at 70 kHz and 120 kHz. We estimated krill biomass using echosounder data collected at 120 kHz and water flow using the ADCP data. We estimated the biomass flux from the product of mean volumetric krill density and flow speed over a depth-integration range of 150 m. The overall mean krill areal biomass density based on hourly averages was 174 g·m-2 during the austral summer (December-March). Mean daily biomass decreased by an order of magnitude, from 300 to 31 g·m-2, over the sampling period, and fluctuated by nearly a factor of 4 above and below the local trend within weekly intervals. Mean current direction was along-shelf toward the west, and mean flow speed increased from ~ 0.10 to 0.14 m·s-1 during the season. Krill flux was correlated with biomass variation, and the grand mean flux was 0.13 g·m-2·s-1. During the study period and in our approximately 1300 km2 study area, average total biomass of krill was 116265 metric tons, and total cumulative krill biomass was 2.5 million tons. Our results demonstrate the utility of integrated echosounder-ADCP systems for quantifying krill flux in an important foraging area used by krill-dependent predators (seabirds and marine mammals) that breed nearby and highlight the scales of variability in a key prey resource required by these predators.